Application of Hydrogen Peroxide as an Innovative Method of Treatment for Legionella Control in a Hospital Water Network - Casini, Beatrice (Pathogens, 2017)
Objectives: To evaluate the effectiveness of hydrogen peroxide (HP) use as a disinfectant in the hospital water network for the control of Legionella spp. colonization. Methods: Following the detection of high levels of Legionella contamination in a 136-bed general hospital water network, an HP treatment of the hot water supply (25 mg/L) was adopted. During a period of 34 months, the effectiveness of HP on Legionella colonization was assessed. Legionella was isolated in accordance with ISO-11731 and identification was carried out by sequencing of the mip gene. Results: Before HP treatment, L. pneumophila sg 2–15 was isolated in all sites with a mean count of 9950 ± 8279 cfu/L. After one-month of HP treatment, we observed the disappearance of L. pneumophila 2–15, however other Legionella species previously not seen were found; Legionella pneumophila 1 was isolated in one out of four sampling sites (2000 cfu/L) and other non-pneumophila species were present in all sites (mean load 3000 ± 2887 cfu/L). Starting from September 2013, HP treatment was modified by adding food-grade polyphosphates, and in the following months, we observed a progressive reduction of the mean load of all species (p < 0.05), resulting in substantial disappearance of Legionella colonization. Conclusion: Hydrogen peroxide demonstrated good efficacy in controlling Legionella. Although in the initial phases of treatment it appeared unable to eliminate all Legionella species, by maintaining HP levels at 25 mg/L and adding food-grade polyphosphates, a progressive and complete control of colonization was obtained.